143 Massive Intra-Hepatic Subcapsular Liver Haematoma Post-Laparoscopic Cholecystectomy- A Rare Complication of a Common Procedure'. (12th October 2021) - Saad, E; O'Connell, L; Khan, I; Barry, K
Abstract: : Laparoscopic Cholecystectomy (LC) is currently considered the gold standard for the management of symptomatic gallbladder stones disease. Specific complications remain challenging, particularly postoperative bleeding, bile leak, and bile duct injury. We report a rare case of a giant intrahepatic subcapsular haematoma (ISH) complicating LC. Case Presentation: A 59-year-old female presented with symptomatic biliary colic. Her past medical history was noted for obesity (BMI>50). She underwent an elective LC with an uncomplicated intraoperative course; however, post-operatively she developed hypovolaemic shock with an acute haemoglobin drop requiring fluid resuscitation and blood transfusion. Emergency CT revealed a massive subcapsular haematoma measuring 21cm×3.1cm× 17cm at the right liver margin without evidence of ongoing bleeding. She was managed conservatively- as per a tertiary hepatobiliary surgery centre's advice- with meticulous clinical observations, serial monitoring of haemoglobin, and repeat CT to assess for interval progressions. She progressed well with conservative management and did not require surgical or radiological intervention. A follow-up liver sonography performed eight weeks post-discharge confirmed a complete resolution. Conclusion: Giant ISH is an exceedingly rare but life-threatening complication following LC which merits special attention. Our case demonstrates the necessity of close postoperative monitoring of patients undergoing LC and considering the possibility of ISH in those who experience refractory postoperative hypotension. It also highlights the decisive role of diagnostic imaging in securing a timely and accurate diagnosis of post-LC ISH.